Analisis Ketetapan Waktu Pada Pembangunan Gedung Pelayanan Terpadu Universitas Tribhuwana Tunggadewi Malang Dengan Metode Earned Value - Ama, Yantonius Tamu ; Suhudi; Arifianto , Andy Kristafi (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
Analysis of project time management control data, and cost control begins with the calculation of BCWP (Budgeted Cost of Work Performanced) values, BCWS (Budgeted Cost of Work Performanced), SV (Shedule Variance), and SPI (Shedule Performance Index), and ECD (Estimate Completion Date). With the Concept of Earned Value During the implementation of the project from week 1 to week 31 there is no deviation between the planned project schedule and the implementation of the project, the estimated cost of completion of the project at week 31 worth IDR. 3,202,207,000.00, and the remaining funds are worth IDR. 83,793,000.00 used for jobs with 1 week remaining, which is at 32nd week worth IDR. 3,286,000,000.00, the project completion time project is in accordance with the initial plan of the project, which is 208 days